SP/RULINA (ARTHROSPIRA): AN EDIBLE MICROORGANISM: A REVIEW - Martba Sáncbez; Jaime Bernal-Castillo; Camilo Rozo; Ignacio Rodríguez (Universitas Scientiarum)
Spirulina is a photosynthetic, filamentous, helical-shaped, multicellular and green-blue microalga. The two most important species of which are Spirulina maxima and Spirulina platensis. For these microórgarusms cell division occurs by binary fission. Since this material contains chlorophyll a, Jike higher plants, botanists classify it as a microalgae belonging to Cyanophyceae class; but according to bacteriologists it is a bacteria dueto its prokaryotic structure. Before Columbus, Mexicans (Aztecs) exploited this microorganism as human food; presently, African tribes (Kanembu) use it for the same purpose. Its chemical composition includes proteins (55%-70%), carbohydrates (15%-25%), essential fatty acids (18%), vitamins, minerals and pigments like carotenes, chlorophyll a and phycocyanin. The last one is used in food and cosmetic industries. Spirulina is considered as an excellent food, lacking toxicity and having corrective properties against viral attacks, anemia, tumor growth and malnUtrition. It has been reported in literature that the use of these microalgae as animal food supplement implies enhancement of the yellow coloration of skin and eggs yo !k in poultry and flaDlÍOgos, growth acceleration, sexual maturation and increase of fertility in cattle.